The Effect of Discovery Learning Learning Model On Critical Thinking Ability In Class 5 Elementary School Students - Arif Mahya Fanny; Moudy Claudia Rahman (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine effect of discovery learning model is the learning ability of students of class V student at SDN Tenggilis Mejoyo I Surabaya. The research method used is a quantitative with research draft Quassi Experimental Design-Posttest Only Control design. The sample in this study is all learners of class 5, using saturated Sampling. Data collection techniques using tests and observations. The instrument in this study is a test sheet of critical thinking and observation sheets of student activity. Data analysis techniques using test-t and percentage. The results of data analysis shows that the application of the discovery learning model can have an effect on students in critical thinking by carrying out all activities according to the steps or syntax specified in the discovery learning model to the critical thinking skills of students at SDN Tenggilis Mejoyo I Surabaya, the results of calculations using the t-test formula obtained a t value of 9.78. Result from the test criteria because 9,78>2,30 or 9.78, then H_0 it is rejected. This means that there is a difference, so there is an effect of this discovery learning model on the critical thinking skills of fifth grade students at SDN Tenggilis Mejoyo I Surabaya. and showed that students activities in The Science learning process using the Discovery learning model were excellent.